Pengembangan Permainan Papa Bolistik Untuk Pembelajaran Bola Voli Siswa SD (Universitas Negeri Semarang, 2021)
The purpose of this study was to produce papa bolistic game products for elementary school students' volleyball learning and test the effectiveness of these game products. This research is a development research according to Dick and Carrey (Punaji Setyosari, 2010: 201) development procedures including: conducting needs analysis, analyzing learning, analyzing learners and context, describing general objectives into more specific objectives, developing assessment instruments, developing strategies learning, developing and selecting learning materials, designing and conducting formative evaluations, making revisions, conducting summative evaluations. Data collection was carried out using expert evaluation sheets, student questionnaire sheets, and observation sheets. The data analysis technique used is descriptive percentage. The subject of the I / small group trial involved 14 students and 41 students for the II / large group trial. The results of the first trial from filling out the questionnaire by Physical Education experts and learning experts obtained an average of 85.33%. Based on the predetermined criteria, this aspect fulfills the good criteria (used). The results of the average student assessment questionnaire and rubik obtained 88.08%. Based on the predetermined criteria, this aspect fulfills the good criteria (used). The results of the second trial of filling out the questionnaire by 1 Physical Education expert and 3 learning experts obtained an average of 91%. Based on the predetermined criteria, this aspect fulfills the criteria very well (used). The results of the average student assessment questionnaire and rubik obtained 94.16%. Based on the predetermined criteria, this aspect fulfills the criteria very well (used). The implementation in the ballistic papa game includes: 1) introduction by throwing catch in pairs, 2) playing the ballistic papa game with existing rules, and 3) developing social attitudes in the game. Based on the results of the study, it is concluded that this papa bolistic game product can be used for volleyball learning for fifth grade elementary school students. Suggestion for Physical Education teachers is that the papa bolistic game can be used as an option for effective Physical Education learning and can be used in public elementary schools.